The corporate sector and the current account - Jan Behringer; Till Van Treeck (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2019)
In this paper, we analyze how corporate sector behavior has affected national current account balances in a sample of 25 countries for the period 1980-2015. A consistent finding is that an increase (decrease) in corporate net lending leads to an increase (decrease) in the current account, controlling for standard current account determinants. We disentangle the current account effects of corporate saving and investment and we explore a number of alternative explanations of our results, including incomplete piercing of the "corporate veil", by households, foreign direct investment activities, a temporary crisis phenomenon, and changes in income inequality. We conclude that corporate sector saving is an important driver of macroeconomic trends and that the rise of corporate net lending especially in a number of current account surplus countries has contributed considerably to global current account imbalances. – – In diesem Working Paper untersuchen wir für 25 Länder für den Zeitraum 1980-2015, wie sich das Verhalten des Unternehmenssektors auf nationale Leistungsbilanzsalden ausgewirkt hat. Ein robustes Ergebnis unserer Analyse ist, dass ein Anstieg (Rückgang) im Finanzierungssaldo des Unternehmenssektors mit einem Anstieg (Rückgang) im Leistungsbilanzsaldo einhergeht, wobei für Standarddeterminanten der Leistungsbilanz kontrolliert wird. Wir unterscheiden ferner die Leistungsbilanzeffekte von Veränderungen im Spar- und Investitionsverhalten des Unternehmenssektors und untersuchen verschiedene Erklärungen der Ergebnisse, wie etwa eine unvollständige Durchdringung des "Unternehmensschleiers" durch die privaten Haushalte, ausländische Direktinvestitionen, ein temporäres Krisenphänomen und Veränderungen der Einkommensungleichheit. Die Ergebnisse lassen darauf schließen, dass die Ersparnisbildung im Unternehmenssektor makroökonomische Trends wesentlich beeinflusst und der Anstieg des Finanzierungssaldos im Unternehmenssektor insbesondere bei einigen Leistungsbilanzüberschussländern erheblich zur Entstehung von globalen Leistungsbilanzungleichgewichten beigetragen hat.
urn:nbn:de:101:1-2019052213015178708307
Keywords: D15; E21; F41; G35; 330; Corporate sector; sectoral financial balances; current account determinants